Reducing the carbon intensity of international shipping – The impact of energy efficiency measures. (November 2022) - Sou, Weng Sut; Goh, Tian; Lee, Xin Ni; Ng, Szu Hui; Chai, Kah-Hin
Abstract: The International Maritime Organisation (IMO) has set a target to reduce the carbon intensity of shipping, or CO2 emissions per transport work, by at least 40% by 2030 from 2008 levels. While short-term measures which focus on improving energy efficiency have been implemented, their impact on carbon intensity trends of international shipping over time has not been quantified. This study quantifies and attributes the contribution of various driving factors to the overall change in carbon intensity of international shipping by ship type. The carbon intensity changes of each ship type are quantitatively linked to the overall carbon intensity target of the IMO. The study results highlight that reductions in carbon intensity at the ship-type and global level have been largely a result of decreases in energy intensity from 2012 to 2018 but reductions became smaller in the later period (2015–2018), underscoring the limits to energy efficiency measures. Furthermore, this study highlights the additional insights that can be drawn on the transport mode and freight activity profiles from the joint analysis of demand and supply-side indicators, revealing not only the changes in freight activity and capacity utilization, but also the shifts in capacity miles travelled for different shipping modes. Highlights: Driving factors of carbon intensity indicators of shipping are analysed quantitatively. Improvements in energy intensity have led to reductions in the carbon intensity. Contributions from energy efficiency have diminished in the more recent period. A joint analysis of supply and demand side indicators offers new insights for decarbonization.